Spatial Patterns of Thalassia testudinum Immune Status and Labyrinthula spp. Load Implicate Environmental Quality and History as Modulators of Defense Strategies and Wasting Disease in Florida Bay, United States - Duffin, Paige; Martin, Daniel L.; Furman, Bradley T.; Ross, Cliff (Frontiers in Plant Science, 2021)
Seagrass wasting disease, caused by protists of the genus Labyrinthula, is an important stressor of the dominant macrophyte in Florida Bay, USA, Thalassia testudinum. Florida Bay (FB) exhibits countervailing gradients in plant morphology and resource availability. A synoptic picture of the Thalassia-Labyrinthula relationship was obtained by assessing the activity of four immune biomarkers in conjunction with pathogen prevalence and load (via qPCR) at 15 sites across FB. We found down-regulated immune status paired with moderate pathogen load among larger-bodied host phenotypes in western FB and up-regulated immunity for smaller-bodied phenotypes in eastern FB. Among the highest immune response sites, a distinct inshore-offshore loading pattern was observed, where coastal basins exposed to freshwater runoff and riverine inputs had the highest pathogen loads while adjacent offshore locations had the lowest. To explain this, we propose a simple, conceptual model that defines a framework for testable hypotheses based on recent advances in resistance-tolerance theory. We suggest resource availability has the potential to drive not only plant size, but also tolerance to pathogen load by reducing investment in immunity. Where resources are more scarce, plants may adopt a resistance strategy, up-regulating immunity; however, when physiologically challenged, this strategy appears to fail, resulting in high pathogen load. While evidence remains correlative, we argue that hyposalinity stress, at one or more temporal scales, may represent one of many potential drivers of disease dynamics in FB. Together, these data highlight the complexity of the wasting disease pathosystem and raise questions about how climate change and ongoing Everglades restoration might impact this foundational seagrass species.